2013
DOI: 10.1111/1440-1681.12051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the analgesic efficacy and psychoactive effects of AZD1940, a novel peripherally acting cannabinoid agonist, in human capsaicin‐induced pain and hyperalgesia

Abstract: The aim of the present study was to investigate the effects of AZD1940, a novel peripherally acting cannabinoid CB(1) /CB(2) receptor agonist, on capsaicin-induced pain and hyperalgesia, as well as on biomarkers of cannabinoid central nervous system (CNS) effects. The present study was a randomized, double-blind, placebo-controlled, four-sequence, two-period, cross-over study in 44 male healthy volunteers aged 20-45 years. The effects of two single oral doses of AZD1940 (400 and 800 μg) were compared with plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 40 publications
(122 reference statements)
0
48
0
Order By: Relevance
“…Peripherally restricted CB 1 agonists and/or selective CB 2 receptor agonists deserve attention, since they are expected to minimise unwanted CNS effects mediated via CB 1 receptors. There are reports indicating that selective peripheral CB 1 agonists are effective in controlling conditions, such as chronic neuropathic pain and spasticity in multiple sclerosis (32,33); however, no evidence of analgesic efficacy was observed for a peripherally acting CB 1 /CB 2 receptor agonist in the human capsaicin pain model (34). Selective CB 2 receptor agonists have also undergone clinical trials and found to be beneficial, but unwanted effects, such as immune depression, have prevented their use in the clinic (35,36).…”
Section: Modulation Of the Endocannabinoid Systemmentioning
confidence: 99%
“…Peripherally restricted CB 1 agonists and/or selective CB 2 receptor agonists deserve attention, since they are expected to minimise unwanted CNS effects mediated via CB 1 receptors. There are reports indicating that selective peripheral CB 1 agonists are effective in controlling conditions, such as chronic neuropathic pain and spasticity in multiple sclerosis (32,33); however, no evidence of analgesic efficacy was observed for a peripherally acting CB 1 /CB 2 receptor agonist in the human capsaicin pain model (34). Selective CB 2 receptor agonists have also undergone clinical trials and found to be beneficial, but unwanted effects, such as immune depression, have prevented their use in the clinic (35,36).…”
Section: Modulation Of the Endocannabinoid Systemmentioning
confidence: 99%
“…CB1 antagonists were thought to be promising for the treatment of obesity and metabolic syndrome 110, 111 , but were withdrawn from the market after some patients developed serious psychiatric side effects. Peripherally restricted agonist of CB1 and CB2 were not found to be effective in patients with pain, and produced CNS and cardiovascular side effects 112 . A selective agonist of CB2 was also examined for its analgesic potential and found to be rather ineffective, though well tolerated 113 .…”
Section: Clinical Application Of Ecs Manipulationmentioning
confidence: 99%
“…The same CB1 inhibition of TRPV1 activity has also been documented in rat trigeminal system (Dux, Deàk, Tassi, Sàntha, & Jancso, ): pre‐junctional CB1 agonism modulates TRPV1‐mediated activation of the trigeminovascular nocisensor complex, and their relationship may be implicated in headaches pathophysiology. Other researches in humans underscored divergent results than the ones obtained with animal models: while a CB2 agonist was able to reduce capsaicin‐induced thermal and mechanical hyperalgesia and allodynia in mice (Hohmann, Farthing, Zvonok, & Makriyannis, ), an agonist of CB1 and CB2 failed to suppress capsaicin‐evoked pain manifestations in humans (Kalliomaki et al, ). These conflicting results may reflect a different synaptic modulation exerted by similar mediators in different species.…”
Section: Trp Channels Plasticity and Cross‐talk With Other Mediatorsmentioning
confidence: 99%